PENGARUH LIKUIDITAS, PROFITABILITAS, PERTUMBUHAN ASET TERHADAP STRUKTUR MODAL YANG DIMODERASI UKURAN PERUSAHAAN - Febriyola, Venny; Widyasari, Widyasari (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
This study aims to determine the effect of the relationship between liquidity, profitability and asset growth on capital structure and is moderated by company size in primary consumer sector companies listed on the Indonesia Stock Exchange in 2019-2021. This research uses secondary data. The method used to select the sample was purposive sampling and the valid data were 33 companies. The data processing technique used was multiple regression analysis and moderated regression analysis assisted by the E-Views 12 SV program. The results of this study show that liquidity and profitability have a negative and significant effect on capital structure, asset growth does not have a positive effect on capital structure, company size has a positive effect on capital structure, company size is not able to moderate the effect of liquidity and asset growth on capital structure, but company size is able to moderate the effect of profitability on capital structure. The implication of this research is that managers have an important role in determining funding sources, so managers must pay attention to and understand what factors can affect capital structure, because an optimal capital structure can attract the attention of investors.